Kazantzakis' Philosophical and Theological Thought Reach What You Cannot - Gill, Jerry H. (Springer International Publishing, 2018)
This book explores the philosophical and theological thought of Nikos Kazantzakis. Kazantzakis is a well-known and highly influential Greek writer, having authored such works as Zorba the Greek and The Last Temptation of Christ, among many others. This volume focuses on the over-arching themes of Kazantzakis' work, namely the importance of the natural world, the nature of humanity, and the nature of God, by means of an analysis of his major novels and other writings. Along the way attention is given to the views of the important scholars who have interacted with Kazantzakis's works, including Peter Bien, Darren Middleton, and Daniel Dombrowski. .